Personal growth through classroom English : (What pupils say they get out of English teaching) - Thiel, Louise (Rhodes University, Faculty of Education, Department of Education, 1993)
Guidance and counselling aims to promote the personal growth of the adolescent. However, in the current South African context, it is possible that formalised Guidance instruction and the post of the school counsellor may disappear in many schools as a result of economic rationalisation. If this occurs, the fostering of personal growth will rest with all teachers and it will be vital to utilise all available opportunities. The study of English is one of the areas traditionally seen to promote personal growth, as several aims of English teaching relate to such growth. The purpose of this study is to investigate from the pupil's perspective whether these aims are being fulfilled within 'Model C' CEO schools in order to gauge the potential of English teaching to fulfil the personal growth role of Guidance teaching. Pupils were asked what influence English teaching had on their attitudes and ideas towards life, on themselves and on their development as people. From the data, common themes were established and documented. These themes showed that important aspects of personal growth are indeed fostered by the English teaching of literature, poetry, written work, oral work and visual literacy. This study therefore confirms that English teaching does foster personal growth and that the potential does exist for English teaching to subsume some of the roles of Guidance.
Keywords: Educational counseling; English language -- Study and teaching -- South Africa